Benign recovery of platinum group metals from spent automotive catalysts using choline-based deep eutectic solvents. Issue 2 (3rd April 2022) - Lanaridi, Olga; Platzer, Sonja; Nischkauer, Winfried; Betanzos, Jokin Hidalgo; Iturbe, Ainhoa Unzurrunzaga; Del Rio Gaztelurrutia, Carmen; Sanchez-Cupido, Laura; Siriwardana, Amal; Schnürch, Michael; Limbeck, Andreas; Konegger, Thomas; Bica-Schröder, Katharina
ABSTRACT: The recovery of platinum group metals (PGMs) from secondary raw materials has become a topic of critical importance mainly due to the gradual depletion of their natural resources and their continuously increasing demand. However, the insufficient recovery of PGMs coupled with the negative environmental impact of the state-of-the-art recycling procedures mandate the investigation and development of alternative recovery processes that will assist in minimizing or even eliminating these drawbacks. Herein, we present a process for the extraction of platinum group metals from spent car catalysts relying on benign deep eutectic solvents (DESs). It is demonstrated that with addition of small amounts of an oxidizing agent, deep eutectic solvents can act as excellent leaching media for the quantitative extraction of platinum group metals. Despite its inertness towards acidic and oxidizing agents, Rh can be leached in a considerable amount which can be further increased by physical pre-treatment of the spent car catalyst material. GRAPHICAL ABSTRACT: UF0001